Was Race a Factor in the Outcomes of the Women’s Health Eating and Living Study? - Paxton, Raheem J. (2011)
BACKGROUND: The purpose of this study was to determine whether women participating in the Women’s Healthy Eating and Living (WHEL) Study, exhibited similar dietary changes, second breast cancer events, and overall survival regardless of race/ethnicity. METHODS: This secondary analysis used data from 3013 women self-identifying as Asian Americans, African American, Hispanic, or white and who were randomly assigned to a dietary intervention or comparison group. Changes in dietary intake over time by race/ethnicity and intervention status were examined using linear mixed-effects models. Cox proportional hazards models were used to examine the effects of the intervention on the occurrence of second breast cancer events and overall survival. Statistical tests were 2-sided. RESULTS: African Americans and Hispanics consumed significantly more calories from fat (+3.2%) and less fruit (−0.7 servings/day) than Asians and whites at baseline (all P < 0.01). Overall, intervention participants significantly improved their dietary pattern from baseline to the end of year 1: reducing calories from fat by 4.9% and increasing intake of fiber (+6.6 grams/day), fruit (+1.1 servings/day), and vegetables (+1.6 servings/day) (all P < 0.05). Despite improvements in the overall dietary pattern of these survivors, the intervention did not significantly influence second breast cancer events and overall survival. CONCLUSIONS: Overall, all racial groups significantly improved their dietary pattern over time, but the maintenance of these behaviors were lower among African American women. More research and larger minority samples are needed to determine the specific factors that improve breast cancer-specific outcomes in diverse populations of survivors.